PROPERTIES OF THE STEEL-FIBER-REINFORCEDCONCRETE WITH DISPERSED REINFORCING WIRE FIBER FROM TECHNOGENIC WASTE - Mikhail Vasilyevich Doudkin,; Kim Alina Igorevna,; AndreyVladimirovich Vavilov,; Chernavin Valery Yurievich,; KlimenkoYevgeniy Alexandrovich,; Marek Mlynczak, (Academic Scientific Journal of Chemistry, 2020)
The article presents the results of theoretical and, most importantly, experimental studies of some properties of steel-fiber-reinforcedconcrete reinforced with dispersed reinforcement from industrial wastes, namely, ITEX steel wire fiber from SPA INNOTECH from spent steel ropes, a large number of which are used as raw materials for fiber production, has accumulated in the region with the mining industry (East Kazakhstan region). The result of the research was indicators of tensile strength of fiber-reinforced concrete during bending of samples, characteristics of crack resistance, and impact strength indicators of fiber-reinforced concrete reinforced with fiber from industrial waste. Knowing and demonstrating these characteristics will make it possible to more effectively ensure the possibility of selling a new product on the building materials market. This publication has been carried out as part of the sub-project Technology for Manufacturing Fiber from Technogenic Wastes, funded by the Government of the Republic of Kazakhstan and the World Bank, Project for Stimulating Productive Innovations.